BS EN 61000-3-12 AMD1 FRAG1. Electromagnetic compatibility (EMC). Part 3-12. Limits. Limits for harmonic currents produced by equipment connected to public low-voltage systems with input current >16 A and ≤ 75 A per phase (29th October 2019) - British Standards Institution,
No abstract available